2012
DOI: 10.1074/jbc.m112.414292
|View full text |Cite
|
Sign up to set email alerts
|

The Intrinsically Disordered N-terminal Region of AtREM1.3 Remorin Protein Mediates Protein-Protein Interactions

Abstract: Background: AtREM1.3 is involved in plant immune signaling. Results: The N-terminal region of AtREM1.3 is intrinsically disordered. Conclusion: N-terminal region facilitates protein interactions. Significance: Remorins are dynamic signaling proteins with respect to structure and localization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 57 publications
1
49
0
Order By: Relevance
“…More detail for the interacting proteins can be found in Supplemental Table S2. (Table continues on following page.) the remorin proteins REMORIN1.2 (REM1.2) and REM1.3 (Borner et al, 2005;Marín et al, 2012). A recent study (Levy et al, 2015) demonstrated that SYTA forms ER-PM junctions that are specifically recruited to PD during virus movement.…”
Section: Validation Of the Proteomics Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…More detail for the interacting proteins can be found in Supplemental Table S2. (Table continues on following page.) the remorin proteins REMORIN1.2 (REM1.2) and REM1.3 (Borner et al, 2005;Marín et al, 2012). A recent study (Levy et al, 2015) demonstrated that SYTA forms ER-PM junctions that are specifically recruited to PD during virus movement.…”
Section: Validation Of the Proteomics Approachmentioning
confidence: 99%
“…The tomato (Solanum lycopersicum) REM1.3 is required for the restriction of potato virus X trafficking (Perraki et al, 2012), while the potato REM1.3 affects the ability of the TRIPLE GENE BLOCK1 MP of Potato virus X and other viral MPs to increase PD permeability (Perraki et al, 2014). Several remorins, including Arabidopsis REM1.3, form nonamyloid filamentous structures of 5.7 to 8 nm (Bariola et al, 2004;Marín et al, 2012). These remorins could be linked with the cytoskeleton in superstructures to maintain cell integrity or act as scaffold proteins for signaling and defense mechanisms (Bariola et al, 2004), a process that might occur in combination with the structural RTNLB proteins.…”
Section: Validation Of the Proteomics Approachmentioning
confidence: 99%
“…Phosphorylation state is also known to play an important regulatory role in protein-protein interactions (Marín et al, 2012;Orr, 2012;Ebert et al, 2013). E. coli MscS forms a homoheptameric channel (Bass et al, 2002;Miller et al, 2003a), and MSL10 is likely to form a multimer as well.…”
Section: Preventing or Mimicking Phosphorylation Of The Msl10 N-termimentioning
confidence: 99%
“…The presence of trifluoroethanol (TFE) simulates the hydrophobic condition that can arise upon forming protein-protein interaction and has been used to assess the propensity of IDRs to undergo induced folding (Sun et al, 2010;Marín et al, 2012). The N-terminal domain of BnaDGAT1 was titrated with increasing amounts of TFE followed by CD analysis (Fig.…”
Section: The Bnadgat1 N-terminal Domain Is Not Necessary For Catalysimentioning
confidence: 99%